Alinhamento de estratégias de pós-graduação ao plano nacional de pós-graduação (PNPG) e ao plano nacional de educação (PNE): ações na Universidade Federal de Goiás - Arantes, Lara Izabella Tosta (2016)
Analyzes the situation of the graduate at the Federal University of Goiás, especially if the offer of programs and actions are in accordance with the guidelines and wider and strategic goals contained in PGNP (National Plan for Graduate Studies) and PNE ( National Education plan) in an attempt to get a holistic view of the university, pointing out all the directly influenced sectoral actions or indirectly by institutional graduate policy. The objective of this study is to analyze the alignment between the guidelines contained in the National Education Plan, National Plan for Graduate Studies and Institutional Development Plan at the Federal University of Goiás, observe the improvement points, making a judgment of what is being done today university, proposing a plan of action that will act contributing to the planning of graduate actions developed at UFG and thus contributing to the institutional advancement, consolidated the importance of improving graduate to the expansion and concept university.The methodology also was based on data extracted from analysis of Sucupira platform Capes. The results concluded in the action plan, through a diagnosis of the UFG performs successfully and stock missing or have points of improvements aimed at further harmonization of the expectations of the academic community, the guiding rules of MEC, CAPES and society with regard to educational and technological development